A systematic study of posterior cervical lymph node irradiation with electrons: Conventional versus customized planning - Jankowska, Petra J.; Kong, Christine; Burke, Kevin; Harrington, Kevin J.; Nutting, Christopher (Radiotherapy and oncology, 2007)
High dose irradiation of the posterior cervical lymph nodes usually employs applied electron fields to treat the target volume and maintain the spinal cord dose within tolerance. In the light of recent advances in elective lymph node localisation we investigated optimization of field shape and electron energy to treat this target volume. In this study, three sequential hypotheses were tested. Firstly, that customization of the electron fields based on the nodal PTV outlined gives better PTV coverage than conventional field delineation. Using the consensus guidelines, customization of the electron field shape was compared to conventional fields based on bony landmarks. Secondly, that selection of electron energy using DVHs for spinal cord and PTV improves the minimum dose to PTV. Electron dose–volume histograms (DVHs) for the PTV, spinal cord and para-vertebral muscles, were generated using the Monte Carlo electron algorithm. These DVHs were used to compare standard vs optimized electron energy calculations. Finally, that combination of field customization and electron energy optimization improves both the minimum and mean doses to PTV compared with current standard practice. Customized electron beam shaping based on the consensus guidelines led to fewer geographical misses than standard field shaping. Customized electron energy calculation led to higher minimum doses to the PTV. Overall, the customization of field shape and energy resulted in an improved mean dose to the PTV (92% vs 83% p = 0.02) and a 27% improvement in the minimum dose delivered to the PTV (45% vs 18% p = 0.0009). Optimization of electron field shape and beam energy based on current consensus guidelines led to significant improvement in PTV coverage and may reduce recurrence rates.